Young people and the great recession - Bell, David N.F.; Blanchflower, David G. (Bonn, 2011)
"This article reviews the effects of the Great Recession on youth labour markets. We argue that young people aged 16-24 have suffered disproportionately during the recession. Using the USA and UK as case studies, we analyse youth unemployment using microdata. We argue that there is convincing evidence that the effects of unemployment when young impose costs on individuals and society well into the future. Though the effects of current policies on youth unemployment are uncertain, there is still a strong case for policy intervention to address the difficulties that the young are having in accessing employment."